Autophagy regulates lipid production and contributes to the sebosuppressive effect of retinoic acid in human SZ95 sebocytes. Issue 2 (May 2020) - Seo, Seong Hoon; Jung, Ju Yeon; Park, Keedon; Hossini, Amir M.; Zouboulis, Christos C.; Lee, Sang Eun
Highlights: Autophagy occurs constitutively in the sebaceous gland cells in human skin. Autophagy markers are downregulated in the acne-involved sebaceous glands. Inhibition of autophagy increases lipid accumulation in SZ95 sebocytes. Rapamycin-induced autophagy suppresses stimuli-induced sebaceous lipogenesis. Autophagy mediates the sebosuppressive effect of 13- cis -RA in SZ95 sebocytes. Abstract: Background: Autophagy is a catabolic process for eliminating damaged organelles or proteins to maintain cellular homeostasis. Recently, lipids have been demonstrated to be targets for autophagosomal degradation. Therefore, autophagy might be involved in sebaceous gland homeostasis, however, relevant data are lacking. Objectives: We investigated the role of autophagy in sebaceous lipogenesis and its regulatory mechanisms in human SZ95 sebocytes. We also examined the possible role of autophagy in 13- cis -retinoic acid (13- cis- RA)-mediated sebosuppression. Methods: Autophagy markers expression was examined by immunohistochemistry in normal and acne lesional skin. SZ95 sebocytes were treated with autophagy inhibitors under starvation or treated with a combination of testosterone and linoleic acid (testosterone/LA), with or without autophagy inducer rapamycin or 13- cis- RA. Lipids were assessed by BODIPY and quantitative Nile Red staining. Autophagy‐related gene 7 small interference RNA was used to confirm the role of autophagy on the sebosuppressive effect of rapamycin or 13- cis- RA. Results: Autophagy markers were strongly expressed in the maturing sebaceous gland cells in healthy skin, whereas downregulated in the acne-involved sebaceous glands. Testosterone/LA or insulin-like growth factor-1 inhibited starvation-induced sebocyte autophagy. Pharmacological inhibition of autophagy led to increased sebaceous lipid accumulation. Contrary, rapamycin inhibited the testosterone/LA-induced lipogenesis and expression of fatty acid synthesis genes via activating the autophagy pathway. 13- cis- RA increased autophagy in SZ95 sebocytes, partly via FoxO1 activation, and inhibition of autophagy abolished the sebosuppressive effect of 13- cis- RA. Conclusions: Autophagy plays an important role in the modulation of lipogenesis in human sebocytes and is involved in the sebostatic effect of 13- cis- RA.